2022
DOI: 10.11005/jbm.2022.29.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Crisis as Presentation of Atypical Parathyroid Adenoma: Two Diagnostically Challenging Cases

Abstract: Atypical parathyroid adenoma (APA) is a rare cause of primary hyperparathyroidism (PHPT) and represents a diagnostic challenge since it is an intermediate form of parathyroid neoplasm of uncertain malignant potential with atypical histological features that require differential diagnosis of parathyroid carcinoma (PC). We present 2 cases of parathyroid crisis as a presentation of APA. The first case was that of a 56-year-old man with parathyroid crisis, constitutional syndrome, and anemia, with evidence of APA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…This was a 56-year-old male (also associating anemia) who developed a 6-month HBS after en bloc resection. The authors reported a similar case of atypical PT adenoma on a 64-year-old female presented for a PT crisis and an acute form of a chronic renal damage as onset of PHPT; she underwent a selective PTx with persistent HPT and no HBS, suggesting that persistent HPT might be the opposite scenario for the patients who develop HBS [48]. Generally, a PT crisis is an extremely severe and rare complication of hormonal anomalies in PHPT.…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 97%
See 4 more Smart Citations
“…This was a 56-year-old male (also associating anemia) who developed a 6-month HBS after en bloc resection. The authors reported a similar case of atypical PT adenoma on a 64-year-old female presented for a PT crisis and an acute form of a chronic renal damage as onset of PHPT; she underwent a selective PTx with persistent HPT and no HBS, suggesting that persistent HPT might be the opposite scenario for the patients who develop HBS [48]. Generally, a PT crisis is an extremely severe and rare complication of hormonal anomalies in PHPT.…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 97%
“…Additionally, in this category damage or elevated blood urea nitrogen [3 calcium [46]. The second category comes from age for adults (yet, not all authors agree) [37,4 case reports) especially brown tumors 58,65,69,70,75,77,88,95,96]; less than convinc oporosis [43] or of a PT crisis [48,71,78]. The self; larger adenomas might have a higher ris [39,82], giant PT adenomas [50,51,78,88], ect…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 99%
See 3 more Smart Citations